Sociodemographic and psychological characteristics influencing patients’ willingness to participate in clinical trials - Gouveia, Rita; Cruz, Vitor Tedim; Almeida, Luís (BMJ open quality, 2022)
Background/AimsClinical trials are fundamental for the development of new medicines and patient participation is based on free consent. Our study sought to identify psychological characteristics that may influence patient willingness to participate in a clinical trial.MethodsA total of 100 participants were invited to participate with 80% positive response rate. The psychological characteristics of each patient were evaluated using the following validated psychometric scales: Self-Efficacy Scale, Curiosity, Exploration Inventory-Trait, Social Support Satisfaction, State-Trait Anxiety Inventory and Social Avoidance and Distress, and Fear of Negative Evaluation.ResultsPatients who agreed to participate in the clinical trial were significantly younger than those who refused (p=0.028). There were no differences in sex, lifestyle, employment status, monthly income or education. After adjusting for age and sex, patients who agreed to participate scored significantly higher in the following: self-efficacy total score (p<0.001), effectiveness in adversity (p<0.001), social effectiveness (p<0.001) and initiation and persistence (p<0.001); social support total score (p<0.001), family satisfaction (p=0.015), friendship satisfaction (p<0.001), social activities satisfaction (p=0.002) and intimacy (p<0.001); total curiosity score (p<0.001), absorption (p<0.001) and exploration (p<0.001). Compared with patients who agreed to participate, those who refused scored significantly higher for both state (p<0.001) and trait anxiety (p<0.001), fear of negative evaluation (p<0.001) and social avoidance and distress (p<0.001).ConclusionsPatients who were willing to participate in clinical trials exhibited different psychological characteristics to patients who refused. Specifically, they were more curious and self-efficacious, less anxious and reported a higher level of social support than patients who declined to participate. Identifying characteristics that condition the individual’s decision to participate in a clinical trial has important implications for the development of patient-focused communication strategies and improved recruitment approaches.